The big adventures of Babymouse. 1, Once upon a messy whisker - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2022)
Babymouse has a BIG imagination that comes to life when she dreams of having straight whiskers.
2.7
3-6
GN490L
Keywords: Babymouse -- (Fictitious character) -- Comic books, strips, etc; Mice -- Comic books, strips, etc; Mice -- Juvenile fiction; Animals -- Comic books, strips, etc; Animals -- Juvenile fiction; Humorous stories; Babymouse -- (Fictitious character) -- Fiction; Mice -- Fiction; Animals -- Fiction; Funny animal comics; Humorous comics; Graphic novels; Comics (Graphic works)